High-strain deformation of conglomerates: Numerical modelling, strain analysis, and an example from the Wutai Mountains, North China Craton. (September 2018) - Ran, Hao; Bons, Paul D.; Wang, Genhou; Steinbach, Florian; Finch, Melanie A.; Griera, Albert; Gomez-Rivas, Enrique; Llorens, Maria-Gema; Ran, Shuming; Liang, Xiao; Zhou, Jie
Abstract: Conglomerates have been widely used to investigate deformation history and rheology, strain, vorticity and viscosity. Previous studies reveal that several factors, such as pebble shapes and concentrations, as well as material properties, affect conglomerate deformation. However, how pebble concentration and interaction between pebbles affect deformation is not understood very well. We use the 2D numerical modelling platform ELLE coupled to the full field crystal visco-plasticity code (VPFFT) to simulate the deformation of conglomerates with various viscosity contrasts between pebbles and matrix and different pebble concentrations, with both linear (stress exponent n = 1) and power-law ( n = 3) viscous rheologies, under simple shear conditions up to a shear strain of ten. Pebbles can behave as effectively passive, deformable or effectively rigid. An increase in pebble concentrations/viscosity contrasts enhances pebble deformation, but reduces their rotation. A mean aspect ratio ( R f ) - orientation ( ϕ ) plot is proposed to gain an estimate of pebble deformation behaviour and the amount of bulk strain. Closely spaced rigid or deformable pebbles can form clusters that mechanically act as single inclusions. Rigid clusters rotate and survive for only short strain increments, whereas the more stable deformable ones keep on elongating with minor rotation. We provide a natural example of deformed conglomerates from the Wutai Mountains, North China Craton. These consist of banded-iron-formation (BIF) pebbles embedded in a schistose matrix. Using the mean R f - ϕ plot, a finite strain of ∼6 under simple shear could be determined. The viscosity of the pebbles is estimated at about 5–8 times that of the matrix for a linear rheology ( n = 1), or 2 to 5 times if a power-law rheology with n = 3 is assumed. Graphical abstract: Image 1 Highlights: Conglomerate deformation is simulated to high shear strain with the ELLE+VPFFT code. Viscosity contrast, pebble concentration and interaction all affect deformation and rotation. Two different types of clusters are investigated: rigid and deformable. A mean Rf-phi plot is proposed to determine strain and viscosity contrast. Strain and viscosity contrast were estimated for deformed conglomerates in the North China Craton.